Faktor-faktor yang Berhubungan dengan Inovasi Asuhan Kebidanan Holistik dalam Pelayanan Praktik Mandiri Bidan di Kota Palembang - Rezah Andriani; Inge Anggi Anggarini; Ria Gustirini (Universitas Baiturrahim, 2023)
Efforts that can be made to reduce interventions in midwifery services are holistic midwifery care. Holistic care is care using a comprehensive concept so that it can detect early and prevent possible complications that will occur immediately. Midwives as health workers who play a role in maternal and child health are expected to be able to provide care with a holistic understanding of women. The innovation of holistic midwifery care in the Independent Practice of the Palembang City Midwife has not been popular among midwives in the City of Palembang. The purpose of this study was to determine the relationship between knowledge, attitudes, motivation, years of service, training, education, and age with holistic midwifery care innovations in midwifery independent practice services in the city of Palembang. This study used a quantitative approach, with an analytic survey design and a cross-sectional design. Statistically there is a significant relationship between knowledge (0.000), attitude (0.028), and training (0.003) with holistic midwifery care innovation in midwifery independent practice services. Statistically, there is no significant relationship between motivation (0.600), years of service (0.705), education (0.161), and age (0.753) with holistic midwifery care innovation in midwifery independent practice services. The variable that has the greatest relationship with holistic midwifery care innovation in midwifery independent practice services is knowledge. The holistic approach is the most comprehensive approach in health care, so midwives are expected to increase their knowledge and attitudes through training related to holistic midwifery care so that they can provide holistic care in midwifery practice.